Viscoelastic Behavior and Thermal Stability of Poly(Lactic Acid) Bio‐Composite Filled with Micro‐Graphite. Issue 1 (22nd June 2020) - Kaavessina, Mujtahid; Distantina, Sperisa; Shohih, Esa Nur; Lomi, Henry Alvin Sebastian; Pratiwi, Betha Putri; Chafid, Achmad
Abstract: Poly(lactic acid) or PLA bio‐composite is prepared by filling with micro‐graphite via solution blending. The micro‐graphite loading is varied from 0–15 wt%. The objectives of this research are to investigate the influence of micro‐graphite loading on PLA bio‐composite, on the viscoelasticity and thermal stability. The viscoelasticity behavior exhibits a considerable dependence on the melt properties of the PLA/micro‐graphite bio‐composites on the percentage micro‐graphite. The complex viscosity |η*|, storage modulus ( G' ), and loss modulus ( G ″) tend to improve with increasing micro‐graphite loading. Thermogravimetric analyses indicate that the micro‐graphite slightly stabilizes the PLA. The decomposition reaction is shifted to a higher temperature in the range 7–9 °C. This reaction leads to the loss of volatile byproducts, which occur at temperatures higher than 310 °C. It means far from the melt processing conditions. The differential scanning calorimetry thermogram shows that the glass transition temperature ( T g ) and the melting temperature are close to that of neat PLA with changes only around 2–4 °C.